Hedonic Shopping Behavior During the Covid-19 Pandemic - Eka Adiputra; Dina Alafi Hidayatin (Journal of International Conference Proceedings, 2022)
People need money during the Covid-19 pandemic as it is today because of the large number of layoffs and unemployment. The government provides cash assistance to people affected by the pandemic. Cash assistance is to ease the economic burden on the community, but it is indicated that the assistance is used to meet hedonic needs. If true, then the program is not as expected by the government. The purpose of this study is to determine whether social assistance funds are used to meet the needs of life or only for hedonic desires. This study was conducted to analyze the effect of hedonic shopping and money available on impulse buying with positive emotion as an intervening variable. The number of samples in the study was 213 respondents. This study uses Partial Least Square (PLS) analysis. The results showed that the effect of hedonic shopping on impulse buying through positive emotion was positively related (os=0.112; p<0.05). The effect of money available on impulse buying through positive emotion is positively related (os=0,270; p<0,05). Positive emotion will further strengthen hedonic shopping and money available in impulse buying. It is recommended that people who receive cash assistance avoid being in the store for too long because they are afraid that they will receive a store stimulus. Initially, maybe people with funds will not do impulse buying, but if they get comfort, tranquillity, and warmth in the store (positive emotion), they will tend to do impulse buying. It is better for people to determine in advance the products they will buy.Keyword:Â impulse buying, cash assisement, consumption